Brain stem death : a chronicle of three decades of search for its cellular and molecular mechanisms - Chan, Samuel H. H. (Translational research in biomedicine / series editor Samuel H.H. Chan, 2022)
Novel clinical biomarker and cellular and molecular mechanisms of brain stem death discovered.